2020
DOI: 10.1200/jgo.19.00261
|View full text |Cite
|
Sign up to set email alerts
|

Can the Adoption of Hypofractionation Guidelines Expand Global Radiotherapy Access? An Analysis for Breast and Prostate Radiotherapy

Abstract: PURPOSE The limited radiotherapy resources for global cancer control have resulted in increased interest in developing time- and cost-saving innovations to expand access to those resources. Hypofractionated regimens could minimize cost and increase access for limited-resource countries. In this investigation, we estimated the percentage cost-savings per radiotherapy course and increased radiotherapy access in African countries after adopting hypofractionation for breast and prostate radiotherapy. For perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 46 publications
2
45
0
1
Order By: Relevance
“…In addition, hypofractionated radiation therapy in many instances should become the standard, decreasing cost and increasing patient convenience while maintaining value in cancer care as shown in a recent study. 19 Fixing infrastructure issues is a long-term challenge that COVID-19 has highlighted. We also acknowledge, despite sharing these experiences, that there is a lack of data on cancer mortality rates during the COVID-19 era, which can provide more perspective compared with prepandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypofractionated radiation therapy in many instances should become the standard, decreasing cost and increasing patient convenience while maintaining value in cancer care as shown in a recent study. 19 Fixing infrastructure issues is a long-term challenge that COVID-19 has highlighted. We also acknowledge, despite sharing these experiences, that there is a lack of data on cancer mortality rates during the COVID-19 era, which can provide more perspective compared with prepandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hypofractionated RT had similar incidence in acute toxicity such as major wound problems, and late sequelae like flap contracture occurred rather less. In addition, in terms of convenience, hypofractionation resulted in higher patient satisfaction, due to the shorter overall duration and reduced cost of hypofractionated RT compared to conventional fractionated RT [ 13 , 14 ]. Therefore, hypofractionated RT has been gradually replacing conventional fractionated RT as a standard of care [ 11 ].Therefore, our results might support the selection of hypofractionated RT in the real world, even considering safety as well as cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…If hypofractionated RT has complication rates that are comparable to conventional fractionated RT, it may become the standard treatment for patients with reconstructed breast cancer. Hypofractionation can be beneficial for patients because it can J o u r n a l P r e -p r o o f reduce the number of visits and the total cost of treatment (13,14). Therefore, this study aimed to identify any difference in breast-related complications between hypofractionated and conventional fractionated RT in breast cancer patients undergoing breast reconstruction.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…The first large RCT offered high-level evidence supporting the noninferior efficacy of postmastectomy HFRT vs CFRT in women with high-risk breast cancer [12]. Generally, if there is no difference in efficacy and toxicities between different fractionated modalities, the reduced fractionation by HFRT in a large cohort of patients can result in substantial savings and increased radiation therapy access [37]. Previous studies have reported that the clinical use of HFRT instead of CFRT after breast-conserving surgery can significantly reduce direct medical costs based on the Medicare paying system in the USA [28,38].…”
Section: Discussionmentioning
confidence: 99%